Enabling At-Homeness for Older People With Life-Limiting Conditions: A Participant Observation Study From Nursing Homes - Lotta Saarnio; Anne-Marie Boström; Ragnhild Hedman; Petter Gustavsson; Joakim Öhlén (SAGE Publishing, 2019)
At-homeness, as an aspect of well-being, can be experienced despite living with life-limiting conditions and needs for a palliative approach to care. In nursing homes, older residents with life-limiting conditions face losses and changes which could influence their experience of at-homeness. The aim of this study was to explore how nursing staff enable at-homeness for residents with life-limiting conditions. Interpretive description was employed as the design using data from participant observations and formal and informal interviews related to nursing care situations. The strategies found to be used to enable at-homeness comprising nursing staff presenting themselves as reliable, respecting the resident's integrity, being responsive to the resident's needs, collaborating with the resident in decision-making, and through nurturing comforting relationships. The result on how to enable at-homeness could be used as strategies for a person-centered palliative approach in the care for residents in nursing homes.